EFFECT OF WORK ENVIRONMENT, WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE AT PT. NUSA MIGHTY GREAT KARIMUN REGENCY - Hizam, Nurul; Indrayani, Indrayani; Catrayasa, I Wayan; Gita Indrawan, Mohamad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This research was conducted to see the influence, environment, motivation and discipline on employee performance through job satisfaction. The research method used is descriptive quantitative which provides an explanation of the description of the research variables. Sampling using convenience sampling technique with a total sample of 90 employees of PT. Mighty Magnificent Shades. The data collection technique used an instrument in the form of a questionnaire for analysis. The instrument was calibrated using item validity and reliability coefficients. Validity was tested using SEM-PLS analysis with the help of SmartPLS software. From the results of the study, it is known that there is an environmental influence on job satisfaction. There is an influence of motivation on job satisfaction. There is no effect of discipline on job satisfaction. There is an environmental influence on performance. There is no influence of motivation on performance. There is an influence of discipline on performance. There is an effect of job satisfaction on performance.